Secondary psychosis induced by metabolic disorders - Bonnot, Olivier; Herrera, Paula M.; Tordjman, Sylvie; Walterfang, Mark (Frontiers in Neuroscience, 2015)
Metabolic disorders are not well recognized by psychiatrists as a possible source of secondary psychoses. Inborn errors of metabolism (IEMs) are not frequent. Although, their prompt diagnosis may lead to suitable treatments. IEMs are well known to paediatricians, in particular for their most serious forms, having an early expression most of the time. Recent years discoveries have unveiled later expression forms, and sometimes, very discreet first physical signs. There is a growing body of evidence that supports the hypothesis that IEMs can manifest as atypical psychiatric symptoms, even in the absence of clear neurological symptoms. In the present review, we propose a detailed overview at schizophrenia-like and autism-like symptoms that can lead practitioners to bear in mind an IEM. Other psychiatric manifestations are also found, as behavioral., cognitive, learning and mood disorders. However, they are less frequent. Ensuring an accurate IEM diagnosis, in front of these psychiatric symptoms should be a priority, in order to grant suitable and valuable treatment for these pathologies.